Carrier Transfer of Deep‐Level Localized States in Type‐II InxGa1−xAs/GaNyAs1−y Short‐Period Superlattice. Issue 1 (3rd October 2019) - An, Xuee; Ma, Chuanhe; Zheng, Xinhe; Hong, Jin; Li, Bo; Sun, Lin; Yue, Fangyu; Chen, Ye
Abstract : Optical properties of InGaAs/GaNAs superlattice are investigated by the photoluminescence and reflectance measurements. A quantum well (QW) emission PM (centered at ≈1.2 eV) and a broad low‐energy emission (LEE) band, which can be resolved to three peaks PA′, PA, and PB (0.77, 0.83, and 0.92 eV) are observed. The peak positions of the LEE exhibit S‐shaped behavior, whereas the QW emission shows a red shift with increasing temperature. The LEE bands are attributed to N‐related deep‐level localized state. The photoluminescence (PL) peak of QW exhibits a significant blue shift and saturation effect with increasing excitation density, which is interpreted in terms of the band‐bending model in the InGaAs/GaNAs short‐period superlattice (SPSL) with a type II band alignment. Furthermore, carrier transfer among these N‐related localized states is elucidated by examining the temperature‐dependent photoluminescence. Such carrier transfer is also demonstrated by the thermal effect under high excitation density. Abstract : The peaks of three N‐related deep‐level localized states and a quantum well (QW) emission are resolved in InGaAs/GaNAs superlattice. Carrier transfer process among different deep‐level localized states is also clearly observed. Based on the large blue shift and saturation effect of QW emission with increasing excitation density, the band alignment of InGaAs/GaNAs superlattice is deduced to be type II.